Vortex Lattice Simulations of Attached and Separated Flows around Flapping Wings - Thomas, Lambert; Abdul Razak, Norizham; Grigorios, Dimitriadis (MDPI, 2017)
Flapping flight is an increasingly popular area of research, with applications to micro-unmanned air vehicles and animal flight biomechanics. Fast, but accurate methods for predicting the aerodynamic loads acting on flapping wings are of interest for designing such aircraft and optimizing thrust production. In this work, the unsteady vortex lattice method is used in conjunction with three load estimation techniques in order to predict the aerodynamic lift and drag time histories produced by flapping rectangular wings. The load estimation approaches are the Katz, Joukowski and simplified Leishman–Beddoes techniques. The simulations’ predictions are compared to experimental measurements from wind tunnel tests of a flapping and pitching wing. Three types of kinematics are investigated, pitch-leading, pure flapping and pitch lagging. It is found that pitch-leading tests can be simulated quite accurately using either the Katz or Joukowski approaches as no measurable flow separation occurs. For the pure flapping tests, the Katz and Joukowski techniques are accurate as long as the static pitch angle is greater than zero. For zero or negative static pitch angles, these methods underestimate the amplitude of the drag. The Leishman–Beddoes approach yields better drag amplitudes, but can introduce a constant negative drag offset. Finally, for the pitch-lagging tests the Leishman–Beddoes technique is again more representative of the experimental results, as long as flow separation is not too extensive. Considering the complexity of the phenomena involved, in the vast majority of cases, the lift time history is predicted with reasonable accuracy. The drag (or thrust) time history is more challenging.